2019
DOI: 10.1002/jcp.28209
|View full text |Cite
|
Sign up to set email alerts
|

LINC00052 functions as a tumor suppressor through negatively modulating miR‐330‐3p in pancreatic cancer

Abstract: Pancreatic cancer is a serious solid malignant tumor worldwide. Increasing evidence has pointed out that abnormal expressions of long noncoding RNAs are involved in various tumors. Meanwhile, LINC00052 is reported as a famous tumor regulator in several cancers. Nevertheless, the biological role of LINC00052 in pancreatic cancer progression is still unknown. Our study was to explore the specific mechanism of LINC00052 in pancreatic cancer. First, we observed that the LINC00052 was obviously downregulated in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
(34 reference statements)
2
15
0
Order By: Relevance
“…Furthermore, miRNAs have involved in lncRNAs. Xiong, X et al [27] demonstrated that linc00052 functioned as a tumor suppressor via negatively regulating miR-330-3p in pancreatic cancer. Instead, linc00858 exerted its function through the suppression of miR-22-3p to promote cells proliferation, migration and invasion [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miRNAs have involved in lncRNAs. Xiong, X et al [27] demonstrated that linc00052 functioned as a tumor suppressor via negatively regulating miR-330-3p in pancreatic cancer. Instead, linc00858 exerted its function through the suppression of miR-22-3p to promote cells proliferation, migration and invasion [28].…”
Section: Discussionmentioning
confidence: 99%
“…Then, online prediction and the dual luciferase reporter gene assay identified that HAGLR could directly bind to miR-330-3p, which was further found to be highly expressed in LC patients. miR-330-3p has been documented to serve as an oncogene in pancreatic cancer [27]. Importantly, previous studies have suggested that miR-330-3p could promote NSCLC LC progression by inhibiting malignant behaviors of LC cells including proliferation, invasion, migration and metastasis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated LINC00472 suppressed the development of cell viability and promoted apoptosis of lung cancer cells by inhibiting miR‐196b‐5p, suggesting a possible therapeutic target in lung cancer treatment 74 . Xiong et al demonstrated that LINC00052 functioned as a tumor suppressor via negatively regulating miR‐330‐3p in pancreatic cancer 75 . It was proved that the LINC00472 expression level could be used as a better disease outcome maker in breast cancer 76 .…”
Section: Crndementioning
confidence: 99%
“…74 Xiong et al demonstrated that LINC00052 functioned as a tumor suppressor via negatively regulating miR-330-3p in pancreatic cancer. 75 It was proved that the LINC00472 expression level could be used as a better disease outcome maker in breast cancer. 76 Zou et al identified that LINC00472 upregulation prevents the cell invasion, metastasis, and growth in NCI-H1299 Cells.…”
Section: Linc00472mentioning
confidence: 99%